Pengaruh Likuiditas Dan Kepemilikan Institusional Terhadap Kebijakan Dividen Perusahaan Manufaktur - Nugraheni, Ni Putu; Mertha, Made (E-Jurnal Akuntansi, 2019)
Investors decide to invest in a company to get a profit in the form of dividends or capital gains. The company must consider the dividend policy that will be made because the decision on dividend distribution will be taken into consideration by investors before making an investment. This study aims to obtain empirical evidence regarding the effect of liquidity and institutional ownership on dividend policy. This research was conducted at a listed manufacturing company in 2014-2017. The method of determining the sample used is using purposive sampling. The data analysis technique used is multiple linear regression. Based on the results of the study, liquidity proxied by the current ratio has a positive and significant effect on dividend policy. Liquidity proxied by cash ratio has a negative and not significant effect on dividend policy. Institutional ownership has a positive and significant effect on dividend policy. Keywords: liquidity, institutional ownership, dividend policy.